Effect of some medicine cancer Cytotoxic Drugs on virulent bacteria E. coli injected in laboratory rats - Tawfiq Al-Hadithi, Hadeel; Abdul Redda Abbas , Yahya (University of Thi-Qar Journal of Science, 2019)
Isolates of E. coli were exposed to sub-minimal inhibitory concentration of each of the cytotoxic drugs MTX, 6-MP, VCR for 4 weeks . Aliquots of 0.5 ml containing 5 x 106 CFU were injected in the peritoneal cavity of Balb/C mice . Results revealed that the bacteria exposed to either MTX & 6-MP were more virulent than those exposed to VCR or those not exposed to any cytotoxic drug . After one hour from injection, the mice demonstrated bacteremia at a ratio of 5/5 then died within 3 days; histopathological examination revealed signs of acute inflammation. Mice injected with bacterial suspension exposed to VCR, have demonstrated symptoms after 3 hours of injection and bacteremia was demonstrated by the ratio of 2/5 and the animals died subsequently, whereas no infection was recorded in mice injected with bacterial suspension not exposed to the cytotoxic drugs and all remained alive.